How to create a breakthrough in consumer-based energy communities in Portugal - brand Identity, service assortment and physical evidence - Marinello, Monica (2023)
In Portugal, Energy Communities are becoming increasingly relevant. Greenvolt Comunidades is a new player in the energy market that focuses on energy management. This report presents a comprehensive marketing strategy for the new service proposed “Poupança Unida”. The document includes an additional report that deeper explores the topic of Brand Identity, the Service Structure and the Service Assortment Roadmap and the current Physical Evidence elements and future opportunities. The objective of the report is to create a breakthrough in consumer-based Energy Communities for Greenvolt Comunidades in Portugal.